Hepatic bipolar radio-frequency ablation between separated multiprong electrodes - Haemmerich, Dieter; Staelin, S. Tyler; Tungjitkusolmun, Supan; Lee, Fred T.; Mahvi, David M.; Webster, John G. (My University, 2001)
Radio-frequency (RF) ablation has become an important means of treatment of nonresectable primary and metastatic liver tumors. Major limitations are small lesion size, which make multiple applications necessary, and incomplete killing of tumor cells, resulting in high recurrence rates. We examined a new bipolar RF ablation method incorporating two probes with hooked electrodes (RITA model 30). We performed monopolar and bipolar in vivo experiments on three pigs. The electrodes were 2.5 cm apart and rotated 45° relative to each other. We used temperature-controlled mode at 95 °C. Lesion volumes were 3.9 ± 1.8 cm 3 (n = 7) for the monopolar case and 12.2 ± 3 cm 3 (n = 10) for the bipolar case. We generated finite-element models (FEMs) of monopolar and bipolar configurations. We analyzed the distribution of temperature and electric field of the finite element model. The lesion volumes for the FEM are 7.95 cm 3 for the monopolar and 18.79 cm 3 for the bipolar case. The new bipolar method creates larger lesions and is less dependent on local inhomogenities in liver tissue-such as blood perfusion-compared with monopolar RF ablation. A limitation of the new method is that the power dissipation of the two probes cannot be controlled independently in response to different conditions in the vicinity of each probe. This may result in nonuniform lesions and decreased lesion size.
Keywords: Bipolar ablation; Electrode; Finite element model; Liver ablation; Radio-frequency; RF ablation